2005
DOI: 10.1091/mbc.e05-07-0626
|View full text |Cite
|
Sign up to set email alerts
|

Functions of Adaptor Protein (AP)-3 and AP-1 in Tyrosinase Sorting from Endosomes to Melanosomes

Abstract: Specialized cells exploit adaptor protein complexes for unique post-Golgi sorting events, providing a unique model system to specify adaptor function. Here, we show that AP-3 and AP-1 function independently in sorting of the melanocyte-specific protein tyrosinase from endosomes to the melanosome, a specialized lysosome-related organelle distinguishable from lysosomes. AP-3 and AP-1 localize in melanocytes primarily to clathrin-coated buds on tubular early endosomes near melanosomes. Both adaptors recognize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
344
1
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 234 publications
(378 citation statements)
references
References 65 publications
(94 reference statements)
26
344
1
7
Order By: Relevance
“…Consistently, Tyr is largely (but not completely) missorted in melanocytes derived from human HPS type 2 patients and HPS model pearl mice that bear mutations in the gene encoding the ␤3A subunit of AP-3 (Huizing et al, 2001;Theos et al, 2005). By contrast, the acidic dileucine-based sorting signal in Tyrp1 has been shown to bind AP-1 but not AP-3 (Theos et al, 2005), and accordingly Tyrp1 accumulates normally on melanosomes in AP-3-deficient melanocytes (Huizing et al, 2001;Setty et al, 2007) (although an unusually large cohort cycles through the plasma membrane; Di Pietro et al, 2006). These results corroborate the dependence on AP-1 and AP-3, respectively, for in vitro budding of Tyrp1 and tyrosinase from Golgi/endosomal membrane fractions (Chapuy et al, 2008).…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…Consistently, Tyr is largely (but not completely) missorted in melanocytes derived from human HPS type 2 patients and HPS model pearl mice that bear mutations in the gene encoding the ␤3A subunit of AP-3 (Huizing et al, 2001;Theos et al, 2005). By contrast, the acidic dileucine-based sorting signal in Tyrp1 has been shown to bind AP-1 but not AP-3 (Theos et al, 2005), and accordingly Tyrp1 accumulates normally on melanosomes in AP-3-deficient melanocytes (Huizing et al, 2001;Setty et al, 2007) (although an unusually large cohort cycles through the plasma membrane; Di Pietro et al, 2006). These results corroborate the dependence on AP-1 and AP-3, respectively, for in vitro budding of Tyrp1 and tyrosinase from Golgi/endosomal membrane fractions (Chapuy et al, 2008).…”
Section: Introductionmentioning
confidence: 76%
“…The acidic dileucine signal in Tyr mediates an interaction with both AP-3 and AP-1 (Honing et al, 1998;Theos et al, 2005), whereas the corresponding signal in Tyrp1 has been shown to interact with AP-1 only (Theos et al, 2005). We therefore used an affinity "pull-down" assay to test whether the dileucine motifs in the OCA2 cytoplasmic domain can be recognized by heterotetrameric adaptors.…”
Section: Oca2 Binds Adaptors Ap-1 and Ap-3 In A Dileucinedependent Mamentioning
confidence: 99%
See 3 more Smart Citations